2007
DOI: 10.1002/chem.200601161
|View full text |Cite
|
Sign up to set email alerts
|

2,2′‐Biphosphinines and 2,2′‐Bipyridines in Homoleptic Dianionic Group 4 Complexes and Neutral 2,2′‐Biphosphinine Group 6 d6 Metal Complexes: Octahedral versus Trigonal‐Prismatic Geometries

Abstract: The geometric and electronic structure of formally d(6) tris-biphosphinine [M(bp)(3)](q) and tris-bipyridine [M(bpy)(3)](q) complexes were studied by means of DFT calculations with the B3LYP functional. In agreement with the available experimental data, Group 4 dianionic [M(bp)(3)](2-) complexes (1P-3P for M=Ti, Zr, and Hf, respectively) adopt a trigonal-prismatic (TP) structure, whereas the geometry of their nitrogen analogues [M(bpy)(3)](2-) (1N-3N) is nearly octahedral (OC), although a secondary minimum was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…The pyridine and aromatic phosphinine rings are essentially coplanar with respect to one another in 4 and 5. The intercyclic C5ÀC6 bonds of 1.470(7)-1.476 (7) are only slightly shorter than in free 2,2'-bipyridine (1.490(3) ), whereas the N À C6 bonds of 1.372(6)-1.386 (6) are slightly longer than the corresponding bond in 2,2'-bipyridine (1.346 (2) ). [19] The P À C bond lengths of 1.711(5)-1.723 (5) are somewhat shorter than in free 2,4,6-triarylphosphinines (1.74-1.76 ), [20] whereas the carbonÀcarbon bond distances in the aromatic phosphinine subunit are in the usual range (1.386(7)-1.413 (7) ) observed for both free and complexed phosphinines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pyridine and aromatic phosphinine rings are essentially coplanar with respect to one another in 4 and 5. The intercyclic C5ÀC6 bonds of 1.470(7)-1.476 (7) are only slightly shorter than in free 2,2'-bipyridine (1.490(3) ), whereas the N À C6 bonds of 1.372(6)-1.386 (6) are slightly longer than the corresponding bond in 2,2'-bipyridine (1.346 (2) ). [19] The P À C bond lengths of 1.711(5)-1.723 (5) are somewhat shorter than in free 2,4,6-triarylphosphinines (1.74-1.76 ), [20] whereas the carbonÀcarbon bond distances in the aromatic phosphinine subunit are in the usual range (1.386(7)-1.413 (7) ) observed for both free and complexed phosphinines.…”
Section: Resultsmentioning
confidence: 99%
“…[4,5] Only a few studies have so far been devoted to its coordination chemistry as this particular ligand requires a multistep synthesis and is, at the same time, difficult to handle due to its high sensitivity towards nucleophilic attack at the phosphorus atom and facile protonation at the nitrogen center. [6] The few examples reported in the literature are complexes of the type [MA C H T U N G T R E N N U N G (NIPHOS)(CO) 4 ] (M= Cr, Mo, W) [7] and Rh I and Ir I dimers of the type [Ir 2 A C H T U N G T R E N N U N G (cod) 2 -A C H T U N G T R E N N U N G (NIPHOS) 2 ][X] 2 and [Rh 2 A C H T U N G T R E N N U N G (nbd) 2 A C H T U N G T R E N N U N G (NIPHOS) 2 ][X] 2 (X = SbF 6 , cod = 1,5-cyclooctadiene, nbd = norbornadiene) [8] in which the phosphinine ligands adopt a m 2 -bonding mode. Latter studies have also shown that NIPHOS binds more strongly to Ir I and Rh I than 2,2'-bipyridine.…”
mentioning
confidence: 99%
“…[14] A related situation seems to explain the trigonal prismatic coordination of Ti, Zr, Hf, and W complexes with biphosphinine (the phosphorous analogue of bipyridine), [51,52] which, according to structural and theoretical studies, are best described as composed of dianionic ligands and d 0 metal ions. [52,53] Finally, two remarkable complexes of d 10 ions with trigonal-prismatic coordination spheres must be noted. One is the [ZnA C H T U N G T R E N N U N G (BH 4 ) 3 ] À ion [55] in which the tetrahydroborate ligands act as bidentate, forming a compressed trigonal prism.…”
Section: Occurrence and Relevance Of The Trigonal Prism As A Coordinamentioning
confidence: 99%
“…A related situation seems to explain the trigonal prismatic coordination of Ti, Zr, Hf, and W complexes with biphosphinine (the phosphorous analogue of bipyridine),51, 52 which, according to structural and theoretical studies, are best described as composed of dianionic ligands and d 0 metal ions 52. 53…”
Section: Occurrence and Relevance Of The Trigonal Prism As A Coordinamentioning
confidence: 99%
“…4,5 However, only a few studies were devoted so far to its coordination chemistry as this particular ligand requires a multistep synthesis and is, at the same time, difficult to handle due to its high sensitivity towards nucleophilic attack at the phosphorus atom and facile protonation at the nitrogen center. 6 The few examples reported in the literature are complexes of the type [M(NIPHOS)(CO) 4 ] (M = Cr, Mo, W), 7 We have recently started to investigate the synthesis and coordination chemistry of functionalized 2,4,6-triarylsubstituted phosphinines, which are generally accessible via the modular pyrylium-salt route. [10][11][12] It turned out that 2-(2 0 -pyridyl)-4,6-diphenyl-phosphinine 1 (Fig.…”
mentioning
confidence: 99%